EXPLORING THE USE OF THE WORDWALL INTERACTIVE MEDIA IN ISLAMIC RELIGIOUS EDUCATION: A QUALITATIVE STUDY IN FORMAL AND NON-FORMAL EDUCATION - Helmi Salma Labibah; Siti Muzayinah; Dinda Ayu Riskiana (Jurnal Konseling Pendidikan Islam, 2026)
The development of digital technology has driven the need for innovative learning media that can increase student engagement in Islamic Religious Education (PAI) learning. One interactive media that is starting to be widely used is Wordwall. This study aims to explore the use of interactive Wordwall media in Islamic Religious Education learning in the context of formal education at SD IT Harapan Bunda and non-formal, namely at Ledug Pintar Learning Guidance. This study uses a qualitative approach with a field study design. The research method uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. Data analysis is carried out through the stages of data reduction, data presentation, and drawing conclusions. The results show that the use of interactive Wordwall media can create a more interesting learning atmosphere, increase active student participation, and help educators in delivering Islamic Religious Education materials in a more varied way. In addition, Wordwall is perceived as a flexible and easily adapted media according to the characteristics of students in formal and non-formal education. However, this study also found several obstacles, including limited access to technology and educators' readiness to optimize media features. This study provides effectiveness that the integration of interactive Wordwall media has the potential to support Islamic Religious Education learning that is more contextual and responsive to students' needs.